El Galeote Mexicano: el atentado contra el obispo José María Cázares, un episodio olvidado de la historia eclesiástica mexicana, 1887-1889 - Bautista Garcia, Cecilia Adriana (Anuario de Historia de América Latina, 2025)
The Mexican newspapers described the attempted assassination of the Bishop of Zamora by a member of the Catholic Church as a true tragedy. The event, which took place on Corpus Christi Thursday in 1887 inside the cathedral of Morelia, had shocked the country’s Catholic society, which was quick to connect the similarities of the case with the murder of the Bishop of Madrid, which occurred just two years earlier at the hands of the priest Cayetano Galeote y Cotilla. During the course of the trial against the accused for attempted murder, the Catholic press encouraged a debate on the possible causes of the event, in light of the social impact of more than two decades of the separation of Church and State, in the context of attacks against other ecclesiastical and civil authorities. In this article we will review the main arguments of this debate.